Benefits and Need of E-Waste Recycling in India - Jethalya, Piyush (Digital Repository of Theses, 2024)
For recycling companies to flourish, consumers must understand the health and ecological risks of electronic garbage. Waste electronics may harm both. Buyers will be motivated by the consequences of not recycling outdated devices. Formal electronic waste management requires current knowledge and recycler-government partnership. If end-user knowledge and cooperation increased, the system would collapse, but the country's electronic waste management rules can't assist with collection and recycling. The system would fail. Compare India's policies to discover coverage gaps. Recycling and consumer surveys are done for this project. Some ignorant Northern Indians had never heard of "e-waste." The research revealed this. Four independent constructs—familiarity with fundamental language, practices, advantages, and challenges—and one dependent construct—total awareness—were discovered using structural equation modelling. This study sought causal links between persons and organisational users. The data was analysed using SPSS and AMOS v20. Four SEM models mediate, while the fifth does not. No model mediates. Unmediated structural equation modelling (SEM) was optimal for India. The results reveal the government must enhance user awareness in all institutions. The SEM was limited to end-users due to the high response rate (five times the questions answered). They had exclusive SEM. Because SEM requirements were not met, regression analysis will examine impacts. Punjab leads, Chandigarh second, Haryana third. Chandigarh leads. Uttar Pradesh ranks fourth, while Himachal Pradesh is least knowledgeable. States compete hard. Another one-way analysis of variance assessed state-level variations in targeted population knowledge. This research says electronic waste's health and environmental effects are unclear. A big knowledge gap exists. India handles just 5% of electronic garbage officially and 95% unofficially. Inefficient electronic waste management. Electronic waste presents serious health and environmental dangers, thus proper treatment and safety are crucial. India has a plan to recycle e-waste. Examples of electronic waste and formal recycling: Pay attention to these four parameters since they will greatly impact the process. Address educational, legislative, electronic waste collection, and obsolete device recycling. Many methods and legislative amendments were recommended to improve end-user knowledge during policy comparison. This research will evaluate electronic waste management regulations, recycler and end user understanding, recycler-state board collaboration, and an effective Indian plan structure.